Build a shaker table [ with Kelly Mehler - Mehler, Kelly; Mastelli, Rick (Taunton Press, 2003)
This DVD shows how to build your shaker style dining table step-by-step, practiced craftsman organizes the entire process of making a traditional leg-and-apron table, from stock selection to finish preparation, choose stock for pleasing grain match, Joint and glue up the top, taper the legs on the jointer, cut the leg mortises with a router, fit the joints and the glue base, size and smooth the top and pin the tenons with square pegs